Teori dan Konsep Objek Material dan Objek Formal Ilmu Manajemen Pendidikan Islam - Refnawati, Refnawati; Apriyenti, Apriyenti; Oktawira, Leni; Jamilus, Jamilus (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This article aims to describe the concept of material and formal objects in Islamic educational management. This study uses the literature study method to review and analyze information from various relevant literature sources, such as scientific journals, books, research reports, and academic articles related to the topic discussed. Data collection techniques are carried out by identifying, collecting, and selecting credible and relevant sources from scientific databases, digital libraries, and other academic repositories. The data analysis technique used in this study is content analysis, where data obtained from literature is systematically analyzed to find patterns, themes, and relationships between the concepts or variables discussed. The results of the analysis show that the material object in Islamic education management refers to everything that is physical and real involved in the educational process. This includes educational institutions, students, educators, curriculum, facilities and infrastructure, as well as learning activities. The formal object in Islamic educational management science is the perspective, principles, and approaches used to manage Islamic educational institutions based on Islamic teachings and values. Principles such as monotheism, sharia, trust, justice, deliberation, as well as efficiency and effectiveness are the main basis in every managerial activity